Potential Use of Umbilical Cord Mesenchymal Stem Cells for Improving Patients with COVID-19: A Review - Motallebzadeh Khanmiri, Jamal; Khani-Eshratabdi, Mohammad; Nasirzadeh, Amirreza; Nematzade, Mahdie; Talebpour, Amir; Mousavi, Seyed Hadi (Archives of Medical Laboratory Sciences, 2021)
The SARS-CoV-2 virus is a member of the coronavirus family that caused the COVID-19 respiratory disease epidemic in China before the global pandemic of the disease in late 2019. The virus’s genome is of 79% similarity to that of the SARS-CoV virus, using the ACE2 receptor to enter its target cells. The most common symptoms of this disease include fever, cough, pulmonary involvement, and sometimes gastrointestinal symptoms. A decline in both the number and function of lymphocytes and a severe increase in leukocyte inflammatory activity are among the most obvious immunological complications of this disease. If the immune system response to the virus is inadequate, the disease can become acute. Immune cells activity leads to a sharp increase in the number of blood cytokines, causing "cytokine storm," which in turn can cause systematic damages to the heart, lungs, and kidneys, and ultimately may lead to death. Mesenchymal stem cell therapy offers a promising approach to reducing the destructive impacts of infection in patients with COVID-19. Mesenchymal stem cells can secrete immune-modulating factors that suppress cytokine storms. Furthermore, the role of mesenchymal stem cells in preventing cell death and inhibiting tissue fibrosis has been well demonstrated. This review shows available clinical trials that have tapped into the therapeutic potential of the umbilical cord mesenchymal stem cells in patients with COVID-19. *Corresponding Author: Seyed Hadi Mousavi; Email: hmousavi@tums.ac.ir; ORCID iD: 0000-0002-0163-5839 Please cite this article as: Motallebzadeh Khanmiri J, Khani-Eshratabadi M, Nasirzadeh A, Nematzade M, Talebpour M, Mousavi H. Potential Use of Umbilical Cord Mesenchymal Stem Cells for the Improving Patients with COVID-19. Arch Med Lab Sci. 2021;7:1-12 (e20). https://doi.org/10.22037/amls.v7.35373